1999
DOI: 10.1086/307450
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Diffuse Cosmic Hard X‐Rays Measured withHEAO 1

Abstract: The spectrum of the diffuse isotropic component of cosmic X-rays over the 13-180 keV range was determined by the UCSD/MIT Hard X-Ray and Gamma-Ray instrument (HEAO A4) on the High Energy Astronomical Observatory-1 (HEAO-1). The instrument consists of a complex of actively shielded and collimated scintillation counters, including the Low Energy Detector set from which the data reported here were obtained. These data join smoothly with the spectrum at lower energies reported by the GSFC HEAO A2 instrument and wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
497
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(524 citation statements)
references
References 33 publications
26
497
1
Order By: Relevance
“…Previously, assumed an X-ray background intensity consistent with the Gruber et al (1999) value increased by 40%, which was well fit by a Comptonthick AGN factor of 1 (flat extrapolation of the N H distribution; Fig. 5).…”
Section: Integral and Swift Hard X-ray Surveyssupporting
confidence: 55%
See 2 more Smart Citations
“…Previously, assumed an X-ray background intensity consistent with the Gruber et al (1999) value increased by 40%, which was well fit by a Comptonthick AGN factor of 1 (flat extrapolation of the N H distribution; Fig. 5).…”
Section: Integral and Swift Hard X-ray Surveyssupporting
confidence: 55%
“…Figure 8b shows the allowed regions in terms of the Compton-thick AGN factor versus reflection parameter. That is, the shaded regions show the values of these two parameters that produce an integrated X-ray background intensity in the 20-40 keV range, the region most affected by both the number of Compton-thick AGN and R, consistent with: (green region) the Gruber et al (1999) data increased by 40% (the maximum suggested renormalization to match higher estimates with imaging instruments at lower energies; Treister & Urry 2005); (red region) the recent INTEGRAL X-ray background intensity measured using Earth occultation by Churazov et al (2006); (blue region) the original Gruber et al (1999) measurements, not renormalized. In each case uncertainties in the X-ray background intensity were assumed to be 5%.…”
Section: Integral and Swift Hard X-ray Surveysmentioning
confidence: 72%
See 1 more Smart Citation
“…The collected normalized dataset of photon fluxes used to place constraints on decaying and annihilating DM in this paper. Data from HEAO-1 [63] (orange), INTEGRAL [64] (green), COMPTEL [65][66][67] (blue), EGRET [68,69] (red), and Fermi [70] (yellow) are shown. All error bars are statistical, except for the EGRET and Fermi datasets, where the dominant systematic uncertainties are shown.…”
Section: Jhep11(2013)193mentioning
confidence: 99%
“…For the HXD/PIN, background spectra were extracted from a time-dependent model provided by the instrument team. Cosmic X-ray background (CXB) flux (Gruber et al 1999) was also included in the PIN background model, at a level of 9.0 × 10 −12 erg cm −2 s −1 , integrated over the 15-50 keV band. The HXD/GSO data are only discussed here in the observations of the two brightest AGN in this sample; in MCG -5-23-16 and NGC 2110 the GSO background was extracted from observations of the clusters Abell 1795 and Fornax respectively.…”
Section: The Suzaku X-ray Observatorymentioning
confidence: 99%